A prognostic score from a multicentric retrospective analysis of patients affected by sarcoma with metachronous lung metastases undergoing metastasectomy. Issue 6 (20th February 2023) - Gallina, Filippo Tommaso; Melis, Enrico; Bertolaccini, Luca; Spaggiari, Lorenzo; Rocca, Michele; Donati, Davide Maria; Chiappetta, Marco; Margaritora, Stefano; Bertoglio, Pietro; Solli, Piergiorgio; Mammana, Marco; Rea, Federico; et al.
Abstract: Background: Despite the lack of evidence‐based on prospective randomized studies, surgery has become the cornerstone of the treatment in patients with pulmonary oligometastatic sarcomas. Our study aimed to construct a composite prognostic score for metachronous oligometastatic sarcoma patients. Methods: A retrospective analysis was performed on data patients who underwent radical surgery for metachronous metastases in six research institutes from January 2010 to December 2018. The log‐hazard ratio (HR) obtained from the Cox model was used to derive weighting factors for a continuous prognostic index designed to identify differential outcome risks. Results: A total of 251 patients were enrolled in the study. In the multivariate analysis, a longer disease‐free interval (DFI) and a lower neutrophil‐to‐lymphocytes ratio (NLR) were predictive of a better overall survival (OS) and disease‐free survival (DFS). A prognostic score was developed based on DFI and NLR data, identifying 2 risk class groups for DFS (3‐years DFS 20.2% for the high‐risk group [HRG]and 46.4% for the low‐risk group [LRG] [<0.0001]) and 3 risk groups for OS (3 years OS 53.9% for the HRG vs. 76.9% for the intermediate‐risk group and 100% of the LRG ( p < 0.0001)). Conclusion: The proposed prognostic score effectively predicts outcomes for patients with lung metachronous oligo‐metastases from the surgically treated sarcoma.